Laporan kinerja lembaga Dewan Perwakilan Daerah Republik Indonesia tahun sidang 2014-2015 - INDONESIA_Dewan_Perwakilan_Daerah_Republik_Indonesia (Dewan Perwakilan Daerah Republik Indonesia, 2015)
st,1/ws.c.1